2004
DOI: 10.1002/cncr.20074
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of the prognosis and treatment of adult brain ependymal tumors

Abstract: BACKGROUNDThe current analysis of outcomes in a large series of adult patients with intracranial ependymal tumors contributes to the characterization of the primary prognostic factors and to the therapeutic management of this rare disease, for which limited information is available in the literature.METHODSThe authors analyzed data on patient and tumor characteristics, treatment, and survival in a series of 70 patients age > 17 years with pathologic diagnoses of brain ependymal tumors from 4 institutions.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
65
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 43 publications
8
65
1
2
Order By: Relevance
“…Age <55 years was associated with a better prognosis in multivariate analysis in terms of OS but not for PFS. These results are consistent with those reported by Reni et al but differ from those reported by Guyotat et al 1,3 These are the only 2 reports in the literature that analyze survival in adult intracranial ependymomas with regard to different age groups. According to the median age of our population 2 cutoff ages were chosen: age 45 years and age 55 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Age <55 years was associated with a better prognosis in multivariate analysis in terms of OS but not for PFS. These results are consistent with those reported by Reni et al but differ from those reported by Guyotat et al 1,3 These are the only 2 reports in the literature that analyze survival in adult intracranial ependymomas with regard to different age groups. According to the median age of our population 2 cutoff ages were chosen: age 45 years and age 55 years.…”
Section: Discussionsupporting
confidence: 91%
“…5,9,18 The prognostic value of histologic findings remains a controversial issue that most likely is attributable to sample size, variability in the definition of anaplasia, discrepancies in histologic diagnoses, and the inclusion in some series of ependymoblastomas and subependymomas, which exhibit different biologic behavior and should be analyzed separately. 1,4,5,9,[19][20][21][22] It is important to emphasize that, in the current study, 57 of 103 patients (55.3%) initially had an incorrect diagnosis of ependymoma. Four classes of pathologic misdiagnoses can be distinguished.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…32 Anaplastic histology was found in 62% of hemispheric ependymomas, a larger percentage than previously reported for intracranial ependymomas (23%-54%). 2,14,21,38,46,47,53 Several series have also found a higher percentage of WHO Grade III tumors in hemispheric ependyomas. 9,22,47,55 Guyotat and colleagues found that all 10 hemispheric ependymomas in their case series of 34 intracranial ependymomas had WHO Grade III pathology.…”
mentioning
confidence: 97%
“…8,9,[19][20][21][22][46][47][48]54 Evidence supports the idea that supratentorial ependymomas have a worse prognosis than infratentorial tumors do in adults. 9,19,20,23,38,45,46 Additional data indicate that patients with hemispheric ependymomas have decreased PFS and OS compared with tumors occurring in the third or lateral ventricles. 9,45 Although often considered an intraventricular tumor, more than half of supratentorial epabbreviatioNs EOR = extent of resection; GTR = gross total resection; OS = overall survival; PFS = progression-free survival; STR = subtotal resection.…”
mentioning
confidence: 99%